A Novel Neutrophil-Based Biomarker to Monitor Disease Activity and Predict Response to Infliximab Therapy in Patients With Ulcerative Colitis - Zhou, Zhou; Zhang, Yinghui; Pan, Yan; Yang, Xue; Li, Liangping; Gao, Caiping; He, Chong (Frontiers in Medicine, 2022)
Background Ulcerative colitis (UC) is characterized by refractory and recurrent mucosal inflammation, leading to a substantial healthcare burden. Diagnostic biomarkers predicting disease activity and treatment response remain elusive. To evaluate the application value of a novel neutrophil-based index (the neutrophil-to-albumin ratio, NAR) as a novel diagnostic biomarker in patients with UC and a predictive marker for disease activity and response to infliximab (IFX) therapy. Methods Clinical characteristics and laboratory parameters of enrolled subjects (patients with UC and healthy controls) were retrieved from the electronic medical record database of our hospital. Serum cytokine and fecal calprotectin levels were measured by enzyme-linked immunosorbent assay (ELISA). Mucosal expression levels of inflammatory agents were measured by quantitative RT-PCR (qRT-PCR). Results We found that NAR, which had not yet been explored in UC, was significantly increased in patients with UC (n = 146) compared to that in controls (n = 133) (1.95 ± 0.41 vs. 1.41 ± 0.23, p < 0.0001). NAR showed a positive association with the disease activity and inflammatory load in patients with UC. Pre-treatment NAR was significantly lower in IFX responders than that in non-responders (2.18 ± 0.29 vs. 2.44 ± 0.21, p = 0.0118), showing a significant ability to discriminate initial responders from primary non-responders to IFX induction therapy (AUC = 0.7866, p = 0.0076). Moreover, pre-treatment NAR predicted postinduction serum IFX trough level. Conclusion Our study provides evidences to utilize NAR in the diagnosis, activity monitoring, and IFX response prediction in patients with UC.